The relationship between R&D subsidy and R&D cooperation in eco-innovative companies: An analysis taking a complementarity approach - Manuel Guisado-González; María del Mar Rodríguez-Domínguez; Mercedes Vila-Alonso; Encarnación González-Vázquez (European Research on Management and Business Economics (ERMBE), 2021)
We analyze whether eco-innovation has a positive or negative influence on the business performance of companies and, through the complementarity approach, whether the joint implementation of R&D subsidy and R&D cooperation increases or decreases the sum of their respective individual impacts on the business performance. If the joint implementation is substitutive, business performance will be lower than potentially possible, so granting R&D subsidies under the condition of establishing R&D cooperation would not be an adequate policy to promote eco-innovation. The analyses were performed using data from the Technological Innovation Panel (PITEC) of 2013 for Spanish manufacturing companies. Our findings indicate that an eco-innovation-oriented strategy positively affects the labor productivity of companies and that receiving public aid as a consequence of establishing R&D cooperation agreements has a lower effect on labor productivity (non-eco-innovative companies), or the same effect (eco-innovative companies), compared to the sum of the individual impacts of R&D cooperation and R&D subsidy. Consequently, in non-eco-innovative companies the use of subsidized R&D cooperation is inadvisable, while their use in eco-innovative companies is neutral.
Keywords: H23; D62; L25; O32; 650; Complementarity approach; Eco-innovation; R&D cooperation; R&D subsidy